Seasonal and pandemic patterns of Influenza in Portugal - Gonçalves, Paulo (2010)
The National Influenza Reference Laboratory has been collecting data on influenza activity in Portugal since 1957 through the National Influenza Surveillance Programme, including information on clinical and virological characteristics of the disease, allowing the estimation of weekly incidence rates for influenza-like illness (ILI). This information has not only been used by the National Health Authorities for the management of the disease, in its several aspects, but has also been contributing to the study of influenza by the World Health Organisation. Particularly during the past decade, the world had been preparing for a long awaited influenza pandemic, which characteristics could not been foreseen but was feared to have potentially devastating consequences. In April 2009 a new strain of influenza A(H1N1) virus of swine origin disseminated throughout the world, resulting in the first pandemic of the XXI century. To face the increasing number of diagnosis being requested, a Network of Associated Laboratories dedicated exclusively to the diagnosis of the new influenza A(H1N1) pandemic virus was activated in our country. The data on influenza collected over the past two influenza seasons, through the National Influenza Surveillance Programme and the Network of Associated Laboratories, is presented and compared. 2. Materials and methods Over 3000 ILI cases were notified to the National Influenza Reference Laboratory and to the Department of Epidemiology of the National Institute of Health, in the context of the National Influenza Surveillance Programme, from week 38/2008 through week 20/2010. The distribution by age group, gender and region, and the signs and/or symptoms present were analysed. Nasopharyngeal swabs were collected for virological characterisation of influenza viruses circulating during this period. The intensity and duration of the epidemic periods were described based on the weekly incidence rates for ILI and as a function of a defined baseline. From week 17/2009 through week 20/2010, over 53.800 ILI cases and respective biological specimens were also notified and analysed by the Network of Associated Laboratories. 3. Results Seasonal AH1, AH3 and B influenza viruses circulating in Portugal during the 2008/2009 season were replaced by the new influenza A(H1N1) pandemic virus since the beginning of the pandemic in the country on week 17/2009. When considering the data obtained though the National Influenza Surveillance Programme, lower ILI incidence rates, lower percentage of confirmed influenza cases (particularly in the population over 15 years) and fewer symptoms presented at the time of notification were observed during the 2009/2010 pandemic. The large volume of cases analysed through the Network of Associated Laboratories is currently under evaluation and will be presented at a later stage. 4. Conclusions Facing the circulation of a new virus and the threat that this could impose to the population and to the health care system, the total number of ILI cases reported and analysed in our country during the 2009/2010 winter boosted to numbers not seen in previous influenza seasons. It is a fact that the 2009/2010 pandemic has had a significant impact in Portugal in many areas, such as the adoption of health-care regulations, availability of health-care facilities, vaccination strategies, and public action/awareness. However, in terms of pattern of disease, the data collected through the National Influenza Surveillance Programme may reveal a different reality. The data analysed suggests that the 2009/2010 pandemic was milder than the previous influenza seasons. Preliminary analysis of the data collected through the Network of Associated Laboratories appears to corroborate these findings.